Determination of optimum hybrid cooling wet/dry parameters and control system in off design condition: Case study. (25th February 2019) - Golkar, Babak; Naserabad, Sadegh Nikbakht; Soleimany, Fatemeh; Dodange, Mansour; Ghasemi, Amir; Mokhtari, Hamid; Oroojie, Pooria
Highlights: Design and optimization of air cooler. Modeling of off design air cooler control system and wet cooling tower. An overview of hybrid system during the year based on an optimized design. Comparison of the hybrid cooling design based on 3E analysis. Abstract: The consequences of water crisis in terms of political, social and environmental impacts have been motivated in this paper to recognize the hybrid wet/dry cooling systems of power plant in Iran. The existence of temperature constraints for consumers connected to the hybrid cooling tower, Space constraints for the construction of auxiliary system, devoting attention to high Net Present Value (NPV) of the project over the course of 25 years, Returning the appropriate capital, Optimal Design of air cooler and it's desirable performance over the course of a year were the reasons led to use of the genetic algorithm (GA) in this paper. The GA should optimize the design of the air cooler, according to that, at one functional point of a year, the lowest investment costs and the lowest cost of utilization in one year will happen. The cost of utilization in this project including: water consumption (makeup water of the cycle), fan power consumption (wet and dry block of hybrid cooling system), as well as chemical additives to water. The results illustrated that the proposed algorithm usage, applying a proper control system, taking into account the standards in the written code and determining the optimization intervals according to the manufacturer's data could conclude to the design of an air cooler, which can be constructed by inquiring from the manufacturing companies. The results also indicated that optimized design of hybrid cooling tower could reduce water consumption about 63% over the course of one year, return on investment by 5 years, develop NPV up to 40 M€ and enhance steam turbine power.